Application of bispectrum analysis to detect faults in helical geared system. (2021) - Gunasegaran, V.; Amarnath, M.; Chelladurai, H.; Krishna, I.R. Praveen
Abstract: In the mechanized power transmission applications one of the crucial elements used to transmit power/motion is gear. Gear faults developed in rotating machines during operating conditions directly affects the performance of the power transmission system. The vibration/acoustic signal monitoring and analysis techniques extensively used in industry to detect and diagnose the incipient faults developed on the contact surfaces of gear tooth. The vibration/acoustic signals acquired from the gearbox are post processed by using signal-processing techniques to achieve cost-effective manufacturing and enhancement in the performance of rotating machines. This paper describes the results of experimental investigations carried out to detect and diagnose the simulated faults in two stage helical gearbox. The vibration and acoustic signals acquired from the gearbox to extract the fault related features. The bispectrum analysis technique used to detect the local fault simulated on the helical gear tooth. Results provided a better fault diagnostic information rather than conventional frequency spectrum analysis.